"Análisis del cumplimiento de la Norma NTE INEN-ISO/IEC 40500 en las páginas Web de las Universidades Públicas del Ecuador para evaluar su accesibilidad Web. Caso aplicativo: Implementación de la página Web oficial del ICIT´S con la plantilla Tipo A" - Quiñonez Estupiñán, Norman Jackson (2016)
At present, it is difficult to conceive a life away from Internet. This has become a fundamental part of human development and a source of access to a variety of services from anywhere in the world. Current internet technologies offer many opportunities to people with special abilities that are not available through any other means, such as newspapers, magazines, books, etc. , however, if there is not a website very well implemented to have a suitable web accessibility, a segment of the population could be excluded of benefit t from the Internet. For this reason, this research seeks to analyze the compliance with NTE INEN ISO / IEC 40500 standard on the websites of public universities in category A of Ecuador to evaluate web accessibility and implement a web page accessibility provided for UNACH. This research was supported by the guidelines and evaluation criteria of the NTE INEN ISO / IEC 40500, the current standard in Ecuador adapting ISO 40500 the international standard to provide access to the web. The research raised a rating methodology for web pages, the best tools to evaluate the code of the pages and, developers used a manual for analysis of this project, discovering that public universities of Ecuador in category A, don not have the ISO / INEN 40500 Standard for web accessibility completely, and there are errors especially in Principle Robustness, which is the least fulfilled. So SETEDIS, the most public institutions in Ecuador are beginning a process of migrating their websites to new versions with accessibility enabled for users. Keywords: web design, web accessibility, ISO 40500, W3C.